2019
DOI: 10.3390/s19235301
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Ga2O3 Nanowires on Silicon for Ultraviolet Photodetector

Abstract: We investigated the effect of silver catalysts to enhance the growth of Ga2O3 nanowires. The growth of Ga2O3 nanowires on a P+-Si (100) substrate was demonstrated by using a thermal oxidation technique at high temperatures (~1000 °C) in the presence of a thin silver film that serves as a catalyst layer. We present the results of morphological, compositional, and electrical characterization of the Ga2O3 nanowires, including the measurements on photoconductance and transient time. Our results show that highly or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The growth morphologies of gallium oxide were studied on various substrates and at different oxidation temperatures. Previous work has shown that crystalline the Ga 2 O 3 phase was obtained under the same oxidation conditions used in this work [ 2 , 22 ]. Because the oxidation conditions were kept constant in this work, the nanostructures formed during oxidation are primarily related to the substrate.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…The growth morphologies of gallium oxide were studied on various substrates and at different oxidation temperatures. Previous work has shown that crystalline the Ga 2 O 3 phase was obtained under the same oxidation conditions used in this work [ 2 , 22 ]. Because the oxidation conditions were kept constant in this work, the nanostructures formed during oxidation are primarily related to the substrate.…”
Section: Resultsmentioning
confidence: 73%
“…We should mention that the SEM image of the Ga 2 O 3 NWs on SiO 2 /Si was taken at the border between the Ag-coated surface and the SiO 2 surface, which emphasizes the catalyst effect of Ag on the growth of Ga 2 O 3 NWs [ 18 ]. Although, it has been shown that sputtered Ag thin film plays a major role in enhancing wettability of the surface and leads to a homogeneous coating of Ga 2 O 3 nanowires [ 22 ]. Using liquid Ag on the top or bottom of liquid Ga showed a nonuniform coating of silicon or quartz as shown for N-Si and SiO 2 -Si ( Figure 2 and Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations